Day-to-day endurance training periodization of world-class cross-country skiers - Walther, J.; Kocbach, J.; Sandbakk, Ø. (European Journal of Sport Science, 2025)
This study aimed to investigate the day-to-day endurance training periodization of male and female world-class cross-country skiers. Self-reported session-by-session training data from 17 (7 female) world-class cross-country skiers were retrospectively analyzed. The data were separated into general preparation (GP) and competition periods (CP), during which all skiers achieved world-class performance. Daily training volume was categorized as very low (0%-50% of mean daily volume), low (50%-100%), moderate (100%-150%), and high (= 150%). Training load (Training Impulse, TRIMP) was calculated as the product of duration and an intensity factor of 1, 2, or 3 for low-, moderate-, and high-intensity training, respectively. Training volume was distributed as 18%/22%/32%/28% across very low/low/moderate/high volume days during GP, whereas the corresponding distribution during CP was 23%/35%/32%/10%. Shifts in daily TRIMP from GP to CP mirrored changes in training volume. During GP, the acute-to-chronic work ratio (ACWR) was 0.75-1.25 on 69% of the days, with 13% of the days showing lower ratios and 18% higher. During CP, the corresponding values were 69%/19%/12%. Intensive sessions occurred every 3.6 ± 0.3 days during GP compared to every 3.0 ± 0.3 days during CP. Training volumes on the day before intensive sessions were 127 ± 13% (GP) and 99 ± 7% (CP) of the daily mean, whereas the corresponding values for the days after were 116 ± 8% and 87 ± 9%. These data provide new insights into day-to-day periodization in world-class cross-country skiers, highlighting the sequential application of training loads by alternating training days of high volume, elevated intensity every 3-4 days, or reduced training load or rest every 8-9 days, while only 5% combining volume and intensity.